Digitalization of Pesantren: A Perspective From Human Capital - Tonny Yuwanda; Abdi Fadhlan; Mayang Bundo (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
Digital transformation is urgent for every aspect of life today. This is also inseparable from pesantren as Indonesia's centers of Islamic religious education. This study aims to see how the digital transformation process in the human resources field in Islamic boarding schools is. The approach to this research is library research, in which a review of the literature related to the research topic is carried out. The discussion results show that several aspects must be improved, namely 1. Digitizing Human Resource Management Activities, 2. Creative Thinking, Innovative and Collaboration Behavior, 3. Leadership and Digital Transformation, 4. Digital Environment. Transformation in human capital can increase work effectiveness, simplify work and save costs in a sustainable process.